Caries prevalence in 12-year-old children from Germany: results of the 2009 national survey - Pieper, Klaus; Lange, J.; Momeni, Anahita; Schulte, Andreas G. (Community dental health, 2013)
Objective: In 2009, complementary epidemiological studies were conducted in 16 German states. Design: A 2009 cross-sectional oral health survey of children aged 12 years with 5% samples selected using a two-stage random sampling procedure. Subjects: A random selection of 30,943 12-year-olds were examined in schools. Method: DMFT and fissure sealants were recorded following WHO criteria. Caries was diagnosed at the caries into dentine threshold (D3) using the visual method without radiography or fibre-optic transillumination. Statistical evaluation was performed using the software SPSS (v12.0). Results: The proportion of children across Germany with caries experience was 31%. The mean DMFT score was 0.72 and the average Significant Caries Index (SiC) was 2.29. The results showed a wide variation among the different federal states, with mean regional DMFT values ranging from 0.56 to 1.06. Compared to the results obtained in 2004, caries prevalence and caries experience decreased distinctly in this age group. The mean DMFT score for 12-year-olds dropped from 2.44 to 0.72 between 1994 and 2009. The mean DMFT scores were 72.7% lower at the end of the observation period than a few years after the introduction of extensive caries prevention measures in Germany. The mean number of fissure sealed teeth ranged between 2.24 and 3.04. Conclusion: The decrease in caries prevalence observed between 1994 and 2004 continued between 2004 and 2009, although once again inequalities in oral health between federal states were observed.
Gesehen am 24.01.2022